USAHA PELATIHAN KETERAMPILAN DI BIDANG PEKERJAAN KAYU SEBAGAI UPAYA KEBERMANFAATAN ALAT DI SMKN SURABAYA - Ardiani, Dyah Ayu Pangastuti; Widjaya, Andang; Supriyanto , Yunaidi (Jurnal Qua Teknika, 2024)
Basically every human being has the opportunity to become an entrepreneur. Likewise for vocational school students, they are educated to be able to enter directly into the world of work as employees or entrepreneurs. As students in the building sector, this furniture business can become a business field for students after being given technopreneur training and how to work wood. Later, it is hoped that students will be able to develop their potential and create jobs for other people. Utilizing tools and materials that are rarely used for the purpose of creating special extracurricular activities for students who have an interest in becoming technopreneurs will be an added value when students graduate and create additional skills that can become a selling point in the industrial world.